The Future of Sino-Russian Relations - Shokhrukh Ashrafi (Resolusi: Jurnal Sosial Politik, 2019)
Today China and Russia declare the strategic partnership between each other and confidently assure each other in the consistency of their actions and commitment to the mutual growth and win-win cooperation. However, if China’s commitment is visible and evident, same cannot be said about Russia: it has been stagnating for over a decade while China’s fast growing economy has been conquering the markets throughout the world; Russia has been spoiling its relations with all European states, that are obviously, at now, an economic and political power, and even with the former allies (Ukraine, Armenia, Belarus); and Russia is not only unable to solve the domestic problems but even worsening them, considering the racism, xenophobia and poverty problems.